Pollinator visitation data for wild Antirrhinum majus plants, with phenotypic and frequency data. - Ellis, Thomas
Data on pollinator visitation to wild snapdragons in a natural hybrid zone, collected as part of Tom Ellis' PhD thesis (submitted February 2016). Snapdragon flowers have a mouth-like structure which pollinators must open to access nectar. We placed 5mm cellophane tags in these mouths, which are held in place by the pressure of the flower until a pollinator visits. When she opens the flower, the tag drops out, and one can infer a visit. We surveyed plants over multiple days in 2010, 2011 and 2012. Also included are data on phenotypic and demographic variables which may be explanatory variables for pollinator visitation.

Inference of mating patterns among wild snapdragons in a natural hybrid zone in 2012 - Field, David; Ellis, Thomas
Genotypic, phenotypic and demographic data for 2128 wild snapdragons and 1127 open-pollinated progeny from a natural hybrid zone, collected as part of Tom Ellis' PhD thesis (submitted) February 2016). Tissue samples were sent to LGC Genomics in Berlin for DNA extraction, and genotyping at 70 SNP markers by KASPR genotyping. 29 of these SNPs failed to amplify reliably, and have been removed from this dataset. Other data were retreived from an online database of this population at www.antspec.org.
Keywords: paternity assignment; pedigree; matting patterns; assortative mating; Antirrhinum majus; frequency-dependent selection; plant-pollinator interaction

Experimental Data for Binding Site Evolution of Bacterial RNA Polymerase - Tugrul, Murat
The data stored here is used in Murat Tugrul's PhD thesis (Chapter 3), which is related to the evolution of bacterial RNA polymerase binding. Magdalena Steinrueck (PhD Student in Calin Guet's group at IST Austria) performed the experiments and created the data on de novo promoter evolution. Fabienne Jesse (PhD Student in Jon Bollback's group at IST Austria) performed the experiments and created the data on lac promoter evolution.
Keywords: RNAP binding; de novo promoter evolution; lac promoter

Fiji script to determine average speed and direction of migration of cells - Hauschild, Robert
This FIJI script calculates the population average of the migration speed as a function of time of all cells from wide field microscopy movies.
Keywords: cell migration; wide field microscopy; FIJI

MATLAB analysis code for 'Sequence-Specific Thermodynamic Properties of Nucleic Acids Influence Both Transcriptional Pausing and Backtracking in Yeast' - Lukacisin, Martin; Landon, Matthieu; Jajoo, Rishi
MATLAB code and processed datasets available for reproducing the results in: Lukačišin, M.*, Landon, M.*, Jajoo, R*. (2016) Sequence-Specific Thermodynamic Properties of Nucleic Acids Influence Both Transcriptional Pausing and Backtracking in Yeast. *equal contributions
Keywords: transcription; pausing; backtracking; polymerase; RNA; NET-seq; nucleosome; basepairing

Synthetic discrete tomography problems - Swoboda, Paul
Small synthetic discrete tomography problems. Sizes are 32x32, 64z64 and 256x256. Projection angles are 2, 4, and 6. Number of labels are 3 and 5.
Keywords: discrete tomography

Tracking, Correcting and Absorbing Water Surface Waves - Bojsen-Hansen, Morten
PhD thesis LaTeX source code

Adaptation to parasites and costs of parasite resistance in mutator and nonmutator bacteria - Wielgoss, Sébastien; Bergmiller, Tobias; Bischofberger, Anna M.; Hall, Alex R. (Molecular Biology and Evolution)
Parasitism creates selection for resistance mechanisms in host populations and is hypothesized to promote increased host evolvability. However, the influence of these traits on host evolution when parasites are no longer present is unclear. We used experimental evolution and whole-genome sequencing of Escherichia coli to determine the effects of past and present exposure to parasitic viruses (phages) on the spread of mutator alleles, resistance, and bacterial competitive fitness. We found that mutator alleles spread rapidly during adaptation to any of four different phage species, and this pattern was even more pronounced with multiple phages present simultaneously. However, hypermutability did not detectably accelerate adaptation in the absence of phages and recovery of fitness costs associated with resistance. Several lineages evolved phage resistance through elevated mucoidy, and during subsequent evolution in phage-free conditions they rapidly reverted to nonmucoid, phage-susceptible phenotypes. Genome sequencing revealed that this phenotypic reversion was achieved by additional genetic changes rather than by genotypic reversion of the initial resistance mutations. Insertion sequence (IS) elements played a key role in both the acquisition of resistance and adaptation in the absence of parasites; unlike single nucleotide polymorphisms, IS insertions were not more frequent in mutator lineages. Our results provide a genetic explanation for rapid reversion of mucoidy, a phenotype observed in other bacterial species including human pathogens. Moreover, this demonstrates that the types of genetic change underlying adaptation to fitness costs, and consequently the impact of evolvability mechanisms such as increased point-mutation rates, depend critically on the mechanism of resistance.

Retrovirus maturation—an extraordinary structural transformation - Mattei, Simone; Schur, Florian; Briggs, John AG (Current Opinion in Virology)
Retroviruses such as HIV-1 assemble and bud from infected cells in an immature, non-infectious form. Subsequently, a series of proteolytic cleavages catalysed by the viral protease leads to a spectacular structural rearrangement of the viral particle into a mature form that is competent to fuse with and infect a new cell. Maturation involves changes in the structures of protein domains, in the interactions between protein domains, and in the architecture of the viral components that are assembled by the proteins. Tight control of proteolytic cleavages at different sites is required for successful maturation, and the process is a major target of antiretroviral drugs. Here we will describe what is known about the structures of immature and mature retrovirus particles, and about the maturation process by which one transitions into the other. Despite a wealth of available data, fundamental questions about retroviral maturation remain unanswered.

On some local topological properties of naive discrete sphere - Sen, Nabhasmita; Biswas, Ranita; Bhowmick, Partha (Computational Topology in Image Context)
Discretization of sphere in the integer space follows a particular discretization scheme, which, in principle, conforms to some topological model. This eventually gives rise to interesting topological properties of a discrete spherical surface, which need to be investigated for its analytical characterization. This paper presents some novel results on the local topological properties of the naive model of discrete sphere. They follow from the bijection of each quadraginta octant of naive sphere with its projection map called f -map on the corresponding functional plane and from the characterization of certain jumps in the f-map. As an application, we have shown how these properties can be used in designing an efficient reconstruction algorithm for a naive spherical surface from an input voxel set when it is sparse or noisy.

On functionality of quadraginta octants of naive sphere with application to circle drawing - Biswas, Ranita; Bhowmick, Partha (Discrete Geometry for Computer Imagery)
Although the concept of functional plane for naive plane is studied and reported in the literature in great detail, no similar study is yet found for naive sphere. This article exposes the first study in this line, opening up further prospects of analyzing the topological properties of sphere in the discrete space. We show that each quadraginta octant Q of a naive sphere forms a bijection with its projected pixel set on a unique coordinate plane, which thereby serves as the functional plane of Q, and hence gives rise to merely mono-jumps during back projection. The other two coordinate planes serve as para-functional and dia-functional planes for Q, as the former is ‘mono-jumping’ but not bijective, whereas the latter holds neither of the two. Owing to this, the quadraginta octants form symmetry groups and subgroups with equivalent jump conditions. We also show a potential application in generating a special class of discrete 3D circles based on back projection and jump bridging by Steiner voxels. A circle in this class possesses 4-symmetry, uniqueness, and bounded distance from the underlying real sphere and real plane.

On the connectivity and smoothness of discrete spherical circles - Biswas, Ranita; Bhowmick, Partha; Brimkov, Valentin E. (Combinatorial image analysis)
A discrete spherical circle is a topologically well-connected 3D circle in the integer space, which belongs to a discrete sphere as well as a discrete plane. It is one of the most important 3D geometric primitives, but has not possibly yet been studied up to its merit. This paper is a maiden exposition of some of its elementary properties, which indicates a sense of its profound theoretical prospects in the framework of digital geometry. We have shown how different types of discretization can lead to forbidden and admissible classes, when one attempts to define the discretization of a spherical circle in terms of intersection between a discrete sphere and a discrete plane. Several fundamental theoretical results have been presented, the algorithm for construction of discrete spherical circles has been discussed, and some test results have been furnished to demonstrate its practicality and usefulness.

Quantum phase magnification - Onur Hosten; Krishnakumar, Rajiv; Engelsen, Nils J; Kasevich, Mark A (Science)
Quantum metrology exploits entangled states of particles to improve sensing precision beyond the limit achievable with uncorrelated particles. All previous methods required detection noise levels below this standard quantum limit to realize the benefits of the intrinsic sensitivity provided by these states.We experimentally demonstrate a widely applicable method for entanglement-enhanced measurements without low-noise detection. The method involves an intermediate quantum phase magnification step that eases implementation complexity. We used it to perform squeezed-state metrology 8 decibels below the standard quantum limit with a detection system that has a noise floor 10 decibels above the standard quantum limit.

Measurement noise 100 times lower than the quantum-projection limit using entangled atoms - Onur Hosten; Engelsen, Nils J; Krishnakumar, Rajiv; Kasevich, Mark A (Nature)
Quantum metrology uses quantum entanglement - correlations in the properties of microscopic systems - to improve the statistical precision of physical measurements. When measuring a signal, such as the phase shift of a light beam or an atomic state, a prominent limitation to achievable precision arises from the noise associated with the counting of uncorrelated probe particles. This noise, commonly referred to as shot noise or projection noise, gives rise to the standard quantum limit (SQL) to phase resolution. However, it can be mitigated down to the fundamental Heisenberg limit by entangling the probe particles. Despite considerable experimental progress in a variety of physical systems, a question that persists is whether these methods can achieve performance levels that compare favourably with optimized conventional (non-entangled) systems. Here we demonstrate an approach that achieves unprecedented levels of metrological improvement using half a million 87Rb atoms in their 'clock' states. The ensemble is 20.1 ± 0.3 decibels (100-fold) spin-squeezed via an optical-cavity-based measurement. We directly resolve small microwave-induced rotations 18.5 ± 0.3 decibels (70-fold) beyond the SQL. The single-shot phase resolution of 147 microradians achieved by the apparatus is better than that achieved by the best engineered cold atom sensors despite lower atom numbers. We infer entanglement of more than 680 ± 35 particles in the atomic ensemble. Applications include atomic clocks, inertial sensors, and fundamental physics experiments such as tests of general relativity or searches for electron electric dipole moment. To this end, we demonstrate an atomic clock measurement with a quantum enhancement of 10.5 ± 0.3 decibels (11-fold), limited by the phase noise of our microwave source.

Engineering spin squeezed states for quantum-enhanced atom interferometry - Engelsen, Nils; Hosten, Onur; Krishnakumar, Rajiv; Kasevich, Mark
We create up to 20 dB spin-squeezed states of atomic ensembles using an optical cavity-based measurement. The prepared states are suitable for atomic sensors that require free space release of the atoms.

Structure of transcribing mammalian RNA polymerase II - Bernecky, Carrie A; Herzog, Franz; Baumeister, Wolfgang; Plitzko, Jürgen; Cramer, Patrick (Nature)
RNA polymerase (Pol) II produces messenger RNA during transcription of protein-coding genes in all eukaryotic cells. The Pol II structure is known at high resolution from X-ray crystallography for two yeast species1-3. Structural studies of mammalian Pol II, however, remain limited to low-resolution electron microscopy analysis of human Pol II and its complexes with various proteins4-10. Here we report the 3.4 Å resolution cryo-electron microscopy structure of mammalian Pol II in the form of a transcribing complex comprising DNA template and RNA transcript. We use bovine Pol II, which is identical to the human enzyme except for seven amino-acid residues. The obtained atomic model closely resembles its yeast counterpart, but also reveals unknown features. Binding of nucleic acids to the polymerase involves 'induced fit' of the mobile Pol II clamp and active centre region. DNA downstream of the transcription bubble contacts a conserved 'TPSA motif' in the jaw domain of the Pol II subunit RPB5, an interaction that is apparently already established during transcription initiation7. Upstream DNA emanates from the active centre cleft at an angle of approximately 105° with respect to downstream DNA. This position of upstream DNA allows for binding of the general transcription elongation factor DSIF (SPT4-SPT5) that we localize over the active centre cleft in a conserved position on the clamp domain of Pol II. Our results define the structure of mammalian Pol II in its functional state, indicate that previous crystallographic analysis of yeast Pol II is relevant for understanding gene transcription in all eukaryotes, and provide a starting point for a mechanistic analysis of human transcription.

Unified scaling of polar codes: Error exponent, scaling exponent, moderate deviations, and error floors - Mondelli, Marco; Hassani, S. Hamed; Urbanke, Rudiger L. (IEEE Transactions on Information Theory)
Consider the transmission of a polar code of block length N and rate R over a binary memoryless symmetric channel W and let P e be the block error probability under successive cancellation decoding. In this paper, we develop new bounds that characterize the relationship of the parameters R, N, P e , and the quality of the channel W quantified by its capacity I(W) and its Bhattacharyya parameter Z(W). In previous work, two main regimes were studied. In the error exponent regime, the channel W and the rate R <; I(W) are fixed, and it was proved that the error probability Pe scales roughly as 2 -√N . In the scaling exponent approach, the channel W and the error probability Pe are fixed and it was proved that the gap to capacity I(W) - R scales as N -1/μ . Here, μ is called scaling exponent and this scaling exponent depends on the channel W. A heuristic computation for the binary erasure channel (BEC) gives μ = 3.627 and it was shown that, for any channel W, 3.579 ≤ μ ≤ 5.702. Our contributions are as follows. First, we provide the tighter upper bound μ <;≤ 4.714 valid for any W. With the same technique, we obtain the upper bound μ ≤ 3.639 for the case of the BEC; this upper bound approaches very closely the heuristically derived value for the scaling exponent of the erasure channel. Second, we develop a trade-off between the gap to capacity I(W)- R and the error probability Pe as the functions of the block length N. In other words, we neither fix the gap to capacity (error exponent regime) nor the error probability (scaling exponent regime), but we do consider a moderate deviations regime in which we study how fast both quantities, as the functions of the block length N, simultaneously go to 0. Third, we prove that polar codes are not affected by error floors. To do so, we fix a polar code of block length N and rate R. Then, we vary the channel W and study the impact of this variation on the error probability. We show that the error probability Pe scales as the Bhattacharyya parameter Z(W) raised to a power that scales roughly like VN. This agrees with the scaling in the error exponent regime.

Comparing the bit-MAP and block-MAP decoding thresholds of Reed-Muller codes on BMS channels - Kudekar, Shrinivas; Kumar, Santhosh; Mondelli, Marco; Pfister, Henry D.; Urbankez, Rudiger (2016 IEEE International Symposium on Information Theory)
The question whether RM codes are capacity-achieving is a long-standing open problem in coding theory that was recently answered in the affirmative for transmission over erasure channels [1], [2]. Remarkably, the proof does not rely on specific properties of RM codes, apart from their symmetry. Indeed, the main technical result consists in showing that any sequence of linear codes, with doubly-transitive permutation groups, achieves capacity on the memoryless erasure channel under bit-MAP decoding. Thus, a natural question is what happens under block-MAP decoding. In [1], [2], by exploiting further symmetries of the code, the bit-MAP threshold was shown to be sharp enough so that the block erasure probability also converges to 0. However, this technique relies heavily on the fact that the transmission is over an erasure channel. We present an alternative approach to strengthen results regarding the bit-MAP threshold to block-MAP thresholds. This approach is based on a careful analysis of the weight distribution of RM codes. In particular, the flavor of the main result is the following: assume that the bit-MAP error probability decays as N -δ , for some δ > 0. Then, the block-MAP error probability also converges to 0. This technique applies to transmission over any binary memoryless symmetric channel. Thus, it can be thought of as a first step in extending the proof that RM codes are capacity-achieving to the general case.

Reed-Muller codes: Thresholds and weight distribution - Mondelli, Marco; Kudekar, Shrinivas; Kumar, Santosh; Pfister, Henry D.; Şaşoğlu, Eren; Urbanke, Rüdiger (24th International Zurich Seminar on Communications)
We describe a new method to compare the bit-MAP and block-MAP decoding thresholds of Reed-Muller (RM) codes for transmission over a binary memoryless symmetric channel. The question whether RM codes are capacity-achieving is a long-standing open problem in coding theory and it has recently been answered in the affirmative for transmission over erasure channels. Remarkably, the proof does not rely on specific properties of RM codes, apart from their symmetry. Indeed, the main technical result consists in showing that any sequence of linear codes, with doubly-transitive permutation groups, achieves capacity on the memoryless erasure channel under bit-MAP decoding. A natural question is what happens under block-MAP decoding. If the minimum distance of the code family is close to linear (e.g., of order N/ log(N)), then one can combine an upper bound on the bit-MAP error probability with a lower bound on the minimum distance to show that the code family is also capacity-achieving under block-MAP decoding. This strategy is successful for BCH codes. Unfortunately, the minimum distance of RM codes scales only as √N, which does not suffice to obtain the desired result. Then, one can exploit further symmetries of RM codes to show that the bit-MAP threshold is sharp enough so that the block erasure probability also tends to 0. However, this technique relies heavily on the fact that the transmission is over an erasure channel. We present an alternative approach to strengthen results regarding the bit-MAP threshold to block-MAP thresholds. This approach is based on a careful analysis of the weight distribution of RM codes. In particular, the flavor of the main result is the following: assume that the bit-MAP error probability decays as N−δ, for some δ > 0. Then, the block-MAP error probability also converges to 0. This technique applies to the transmission over any binary memoryless symmetric channel. Thus, it can be thought of as a first step in extending the proof that RM codes are capacity-achieving to the general case.

Magnetic torque anomaly in the quantum limit of Weyl semimetals - Moll, Philip J. W.; Potter, Andrew C.; Nair, Nityan L.; Ramshaw, B. J.; Modic, Kimberly A; Riggs, Scott; Zeng, Bin; Ghimire, Nirmal J.; Bauer, Eric D.; Kealhofer, Robert; Ronning, Filip; Analytis, James G. (Nature Communications)
Electrons in materials with linear dispersion behave as massless Weyl- or Dirac-quasiparticles, and continue to intrigue due to their close resemblance to elusive ultra-relativistic particles as well as their potential for future electronics. Yet the experimental signatures of Weyl-fermions are often subtle and indirect, in particular if they coexist with conventional, massive quasiparticles. Here we show a pronounced anomaly in the magnetic torque of the Weyl semimetal NbAs upon entering the quantum limit state in high magnetic fields. The torque changes sign in the quantum limit, signalling a reversal of the magnetic anisotropy that can be directly attributed to the topological nature of the Weyl electrons. Our results establish that anomalous quantum limit torque measurements provide a direct experimental method to identify and distinguish Weyl and Dirac systems.